(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
Online education has revolutionized the way people learn by providing a convenient, flexible and cost-effective alternative to traditional classroom-based education. With the advancement of technology, students can now access a wide range of courses from prestigious institutes around the world from the comfort of their homes. This shift has not only democratized education, but also allowed people to develop their acquired skills and knowledge at their own pace, making it more accessible to the public, making education more personalized and inclusive. As online education continues to grow, it is changing the way we learn in a big way and offers many benefits and opportunities that meet the diverse needs of today’s students.